Feasibility of Roux-en-Y Gastric Bypass with the novel robotic platform HUGO™ RAS - Raffaelli, Marco; Voloudakis, Nikolaos; Pennestrì, Francesco; Gallucci, Pierpaolo; Modesti, Cristina; Salvi, Giulia; Greco, Francesco; Ciccoritti, Luigi (Frontiers in Surgery, 2023)
Introduction: Robotic assisted surgery is a rapidly developing field of minimally invasive bariatric surgery in the last 20 years. Its wide diffusion has led to the development and standardization of robotic assisted approaches for bariatric operations. In this study, we present the first four Roux-en-Y Gastric Bypass (RYGB) operations performed with the new Hugo™ RAS system (Medtronic, Minneapolis, MN, USA). Methods: In January and February 2023, consecutive patients scheduled for minimal invasive Roux-en-Y-Bypass were randomly selected and underwent the procedure robotic-assisted with the new platform. No exclusion criteria were applied. Results: Four patients, two females and two males, underwent RYGB with a median BMI of 40 (range:36-46) and diabetes mellitus in two cases. The median docking time was 8 min (range: 7-8.5) and the median console time was 127.5 min (range: 95-150). A description of the operating theatre, robotic arms and docking setup is provided. Procedures were performed without intraoperative complications and no conversion to laparoscopy or open surgery was noted. No additional ports were needed to be placed. System’s function and docking were uneventful. No early post-operative complications were observed. Conclusions: Based on our initial experience, RYGB with the Hugo™ RAS system is feasible. This study provides the configurations necessary to perform RYGB with the Hugo™ RAS system as well as general information and insights from our preliminary experience.